PEMENUHAN HAK PARTISIPASI ANAK MELALUI FORUM ANAK DAERAH KABUPATEN BANDUNG DALAM PELAKSANAAN “PROGRAM KABUPATEN BANDUNG LAYAK ANAK” - Andika Subagja, Aria; Anwar, Alii; Gunawan, Uga Pratama (Peksos: Jurnal Ilmiah Pekerjaan Sosial, 2024)
Recently, decision-making regarding children's right to participate has become a major focus in development policies and programs in various regions of Indonesia. One significant initiative in this regard is the "Child-Friendly Regency" (Kabupaten Layak Anak or KLA) program implemented in Bandung Regency through the Children's Forum. This study employs a qualitative method, combining literature review and empirical study, to examine the fulfillment of children's right to participate through the Bandung Regency Children's Forum in the implementation of the Child-Friendly Regency Program. Data was collected through observations, interviews, and relevant literature analysis. The study involved the management of the Children's Forum, the head of the Children's Forum, and the head of the section for children's rights fulfillment in Bandung Regency. The results indicate that Bandung Regency is committed to becoming a Child-Friendly Regency, with various initiatives to involve children in decision-making processes. The Children's Forum serves as an essential platform for children's participation, allowing them to contribute to development planning. However, challenges such as limited funding, a lack of stakeholder understanding, and geographical constraints hinder the program's implementation. To address these challenges, the Bandung Regency government has implemented strategies such as data analysis, the establishment of children's forums at the sub-district and village levels, and intensive socialization to increase understanding of children's participation rights. Cross-sector cooperation with businesses, NGOs, mass media, and academics is also crucial to support the success of the KLA program. Keywords: Children's Rights Fulfillment, Child Participation, Child-Friendly Regency.